2020
DOI: 10.3390/rs12091392
|View full text |Cite
|
Sign up to set email alerts
|

Improving Land Cover Classification Using Extended Multi-Attribute Profiles (EMAP) Enhanced Color, Near Infrared, and LiDAR Data

Abstract: Hyperspectral (HS) data have found a wide range of applications in recent years. Researchers observed that more spectral information helps land cover classification performance in many cases. However, in some practical applications, HS data may not be available, due to cost, data storage, or bandwidth issues. Instead, users may only have RGB and near infrared (NIR) bands available for land cover classification. Sometimes, light detection and ranging (LiDAR) data may also be available to assist land cover class… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 43 publications
0
24
0
Order By: Relevance
“…In JSR, a 3 × 3 or 5 × 5 patch of pixels is used in the S target matrix. The parameter s 0 in Equation (13) of [52] is the design parameter, which controls the number of sparse elements. Details of the mathematics have been described by the authors of [52].…”
Section: Comparison With Conventional Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In JSR, a 3 × 3 or 5 × 5 patch of pixels is used in the S target matrix. The parameter s 0 in Equation (13) of [52] is the design parameter, which controls the number of sparse elements. Details of the mathematics have been described by the authors of [52].…”
Section: Comparison With Conventional Methodsmentioning
confidence: 99%
“…In addition to these two conventional methods, classification results reported by two papers, which used this same dataset with hyperspectral and LiDAR bands augmented with EMAP, were also considered for comparison as well. Details of the JSR and SVM results have been described by the authors of [52].…”
Section: Comparison With Conventional Methodsmentioning
confidence: 99%
“…In many land cover classification papers, researchers use all of the multispectral and hyperspectral bands for classification. Recently, there have been some investigations [17][18][19] that only use a few bands such as RGB and NIR bands, and yet can still achieve reasonable classification accuracy. In [17], it was found that synthetic bands using Extended Multi-attribute Profiles (EMAP) [20][21][22][23] can help improve the land classification performance quite significantly.…”
Section: Of 29mentioning
confidence: 99%
“…This is shown to illustrate how low performing some types are even among the high-performing methods. Table 3, extracted from a recent work [34], corresponds to the accuracy for the full 15 class models while Table 4 is for consolidated 5 classes. Comparing the two tables, it can be seen that the new class combination results in much improved results in all cases.…”
Section: Consolidation Of the Number Of Land Cover Classesmentioning
confidence: 99%